2018
DOI: 10.1002/ente.201700840
|View full text |Cite
|
Sign up to set email alerts
|

Modern Ni and Pd–Ni Catalysts Supported on Sn–Al Binary Oxide for Oxy‐Steam Reforming of Methanol

Abstract: Monometallic Ni and bimetallic Pd–Ni catalysts supported on mono‐SnO2 and SnO2–Al2O3 binary oxide are prepared using a wet impregnation and subsequent impregnation method. The catalysts are tested in oxy‐steam reforming of methanol (OSRM) and characterized. The activity measurements show that palladium‐promoted nickel catalysts supported on SnO2–Al2O3 exhibit high activity, selectivity towards hydrogen formation, and stability. The effect of Pd on reducibility, surface acidity, and morphology of the Ni support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Currently, the depletion of natural fossil fuel resources and rising prices cause that humanity around the world are focused their research interest in development of others source of energy. One of the possible solutions of this problem is fuel cell technology powered by hydrogen easily accessible on earth [1]. The use of hydrogen as an energy raw material is a hot topic for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the depletion of natural fossil fuel resources and rising prices cause that humanity around the world are focused their research interest in development of others source of energy. One of the possible solutions of this problem is fuel cell technology powered by hydrogen easily accessible on earth [1]. The use of hydrogen as an energy raw material is a hot topic for several years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28,34,35 ] The second and third peaks at 400° to 600° can be attributed to the reduction of surface Pd δ+ to Pd interacted with the supports as well as the coreduction of Sn 4+ to Sn 2+ species. [ 27,30,36–39 ] By comparing the Pd‐NbN/C and Pd 1 Sn 3 ‐NbN/C, it can be found that, Sn doping results in obvious negative‐shift of the first (from 62° to 53°) and second (from 470° to 440°) reduction peaks for Pd 1 Sn 3 ‐NbN/C, suggesting that the redox ability of the Pd 1 Sn 3 ‐NbN/C can be further promoted by the introduce of Sn. The promoting effects may be attributed to the hydrogen spillover effects, that is, the dissociated H* species can transfer from Pd to the Sn surface in the Pd 1 Sn 3 ‐NbN/C, suggesting the presence of the evident interaction of PdSn and NbN.…”
Section: Resultsmentioning
confidence: 99%
“…The promoting effects may be attributed to the hydrogen spillover effects, that is, the dissociated H* species can transfer from Pd to the Sn surface in the Pd 1 Sn 3 -NbN/C, suggesting the presence of the evident interaction of PdSn and NbN. [28,30,32,36,38,[40][41][42][43] To sum up, the H 2 -TPR results also support the interfacial interaction in the Pd 1 Sn 3 -NbN/C catalysts, consistent with the XPS analysis, which is also responsible for the enhancement of catalytic performance for EOR. Then, the electrocatalytic performances of the Pd x Sn y -NbN catalysts toward EOR in an alkaline medium are systemically studied, as shown in Figure 4 and Table 1.…”
Section: Characterization Of the Pd X Sn Y -Nbn/c Catalystsmentioning
confidence: 99%
“…As discussed above, the SnO 2 surface is covered by the NiO in the NiO(10%)/ SnO 2 catalyst, and there is an interface formation between the NiO and SnO 2 . 49,50 Therefore, the reduction of NiO species occurs at a higher temperature (than pristine NiO), whereas the reduction of SnO 2 occurs at a lower temperature (than pristine SnO 2 ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%